Empowering Followers as the Dominant Driver of Organizational Performance: Evidence from Kenya’s Water Sector - Gachugia, Joseph Njuguna; Ongeti, Walter Juma; Oduol, Truphena (Human Resource and Leadership Journal, 2026)
Purpose: The purpose of this study was to examine the effect of exemplary transformational leadership on organizational performance among selected water service providers in Kenya, with specific focus on determining whether empowering followers is the most significant driver of performance. Methodology: The study adopted a positivist philosophy and a cross-sectional survey design. Data were collected from 368 employees across 13 water and sewerage companies under the Athi Water Works Development Agency using structured questionnaires. Three leadership practices—modeling the way, challenging the process, and empowering followers were assessed and data analyzed using descriptive statistics, inferential statistic and multiple regression analysis in SPSS version 27. Findings: The findings revealed unequal effects among the leadership practices. Modeling the way had a positive but statistically insignificant effect on performance (β = 0.022, p = 0.779), indicating a primarily foundational role. Challenging the process had a positive and significant effect (β = 0.192, p = 0.016), demonstrating the importance of innovation. Notably, empowering followers emerged as the strongest and most significant predictor of organizational performance (β = 0.391, p < 0.001), confirming it as the dominant leadership practice influencing performance outcomes. Unique Contribution to Theory, Policy, and Practice: The study contributes to theory by advancing an integrative conceptualization of exemplary transformational leadership and providing empirical evidence that its dimensions exert differential effects on performance. It specifically establishes empowering followers as the central mechanism through which leadership translates into organizational outcomes. From a policy perspective, the findings suggest a shift toward empowerment-focused leadership development frameworks in the water sector. Practically, the study highlights the importance of delegation, participatory decision-making, and employee empowerment as key drivers of improved performance in public utilities.